Body-image and -size perception after a single session of HIIT body work in healthy adult men - Rica,Roberta Luksevicius (2018)
It was our objective to analyze the effects of a single session of whole body HIIT on body-image and -scheme parameters of healthy adult men. Twenty-one active, healthy adults performed high-intensity intermittent training based on full body exercise. The training session involved 20 sets of 30?second all-out exercise and 30 seconds of passive recovery between sets. All subjects underwent blood lactate measurement, rate of perceived exertion, feeling scale and body image assessment and perception of body size measurements. Significant differences (p<0.001) were found on blood lactate but not in feeling scale. The values of current and adequate silhouette did not differ between each other and the real silhouette. Significant differences were found on Image Marking Procedure (IMP) (p< 0.003). Additionally, significant differences (p= 0.009) were found on prevalence of adequate, hypoeschematic and hypeschematic. Although alteration was not found on self-perception of body image, a single session of HIIT body work promoted alteration on body size perception in healthy adult men.